2020
DOI: 10.31234/osf.io/r4pxy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between brain structure and general psychopathology in preadolescents

Abstract: Categorical mental disorders are being recognized as suboptimal targets in clinical neuroscience due to poor reliability as well as high rates of heterogeneity within, and comorbidity between, mental disorders. As an alternative to the case-control approach, recent studies have focused on the relationship between neurobiology and latent dimensions of psychopathology. The current study aimed to investigate the relationship between brain structure and psychopathology in the critical preadolescent period when psy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Mental disorder diagnoses were determined using parent or guardian responses to the parent-reported computerized Schedule for Affective Disorders and Schizophrenia for School-Age Children for DSM-5 (K-SADS-5) (35). Lifetime (past or present) diagnoses of the 18 disorders were used (22, 36, 37). Based on the definition of broad diagnostic families adopted in recent studies (36, 38, 39), two broad diagnostic families including externalizing disorders (Attention-Deficit/Hyperactivity Disorder, Oppositional Defiant Disorder, Conduct disorder), internalizing disorders (Dysthymia, Major Depressive Disorder, Disruptive Mood Dysregulation Disorder, Agoraphobia, Panic Disorder, Specific Phobia, Separation Anxiety Disorder, Social Anxiety Disorder, Generalized Anxiety Disorder, Post-Traumatic Stress Disorder) were used in our analysis (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental disorder diagnoses were determined using parent or guardian responses to the parent-reported computerized Schedule for Affective Disorders and Schizophrenia for School-Age Children for DSM-5 (K-SADS-5) (35). Lifetime (past or present) diagnoses of the 18 disorders were used (22, 36, 37). Based on the definition of broad diagnostic families adopted in recent studies (36, 38, 39), two broad diagnostic families including externalizing disorders (Attention-Deficit/Hyperactivity Disorder, Oppositional Defiant Disorder, Conduct disorder), internalizing disorders (Dysthymia, Major Depressive Disorder, Disruptive Mood Dysregulation Disorder, Agoraphobia, Panic Disorder, Specific Phobia, Separation Anxiety Disorder, Social Anxiety Disorder, Generalized Anxiety Disorder, Post-Traumatic Stress Disorder) were used in our analysis (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Mental disorder diagnoses were determined using parent or guardian responses to the parent-reported computerized Schedule for Affective Disorders and Schizophrenia for School-Age Children for DSM-5 (K-SADS-5) (35). Lifetime (past or present) diagnoses of the 18 disorders were used (22,36,37). Based on the definition of broad diagnostic families adopted in recent studies (36,38,39) were used in our analysis (Figure 1A).…”
Section: Definition Of Diagnostic Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual frameworks have suggested a bidirectional relationship between cognitive function and psychopathology ( Batty et al, 2005 ; Calvete et al, 2013 ; Schweizer and Hankin, 2018 ). With the advent of large-scale magnetic resonance imaging (MRI) studies, group differences in the structural properties of the cerebral cortex (predominantly cortical thickness) have been reported in common psychiatric disorders ( Ching et al, 2020 ; Hoogman et al, 2020 ; Thompson et al, 2020 ; Van den Heuvel et al, 2020 ; Patel et al, 2021 ), as well as in relation to general psychopathology ( Mewton et al, 2020 ; Romer et al, 2021a , b ) and cognitive ability ( Shaw et al, 2006 ; Karama et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transdiagnostic research has also reached neuroscience, as demonstrated in the final two papers I focus on from this journal issue. Mewton et al (2022) reported on the relationship between general and specific psychopathology in preadolescents (9-10-year-olds) and brain structure measured using MRI in a community cohort study, the Adolescent Brain and Cognitive Development study. Their variables for general psychopathology as well as externalising, internalising and thought disorder 'lower order' dimensions were derived from a higher-order model of psychopathology using confirmatory factor analysis (for a discussion of the pfactor model of psychopathology, see elsewhere (Caspi & Moffitt, 2018;Ronald, 2019).…”
mentioning
confidence: 99%